Fetal testing in intra-uterine growth retardation - Snijders, R; Hyett, J (Current opinion in obstetrics & gynecology, 1997)
There are three major issues that remain subject to debate in relation to fetal growth retardation: (1) Which method should be used to identify the affected population? (2) Which biophysical test(s) is most appropriate to assess the pregnancy? (3) Which factors are important when considering elective delivery? This review summarizes recent studies investigating the efficacy and accuracy of tests used for the identification and surveillance of pregnancies at risk of growth retardation, and discusses the importance of gestational age in the decision for or against intervention.